Change in Physical Activity and Sedentary Time Associated With 2-Year Weight Loss in Obese Adults With Osteoarthritis - Pellegrini, Christine A. (J Phys Act Health, 2015)
BACKGROUND: We examined if changes in moderate-to-vigorous physical activity (MVPA), light activity, and sedentary behavior are related to weight change over a 2-year period in obese adults with/elevated risk for knee osteoarthritis. METHODS: Weight, physical activity, and sedentary time at baseline and 2 years were obtained from 459 obese participants from the Osteoarthritis Initiative. Weight change was categorized as ≥ 10 lbs, 5.0 to 9.9 lbs, 4.9 to −4.9 lbs, −5.0 to −9.9 lbs, and ≤ −10 lbs. We examined the association between 2-year weight change categories and changes in activity/sedentary time from accelerometer monitoring by multiple linear regression adjusted for baseline weight, demographic, and health factors. RESULTS: Across the 5 weight categories (loss to gain), average 2-year change ranged from −7.4 to 28.0 sedentary minutes/ day, 4.2 to −23.1 light activity minutes/day, and 3.2 to −4.9 MVPA minutes/day, respectively. Higher weight loss categories were separately associated with increased MVPA (P for trend < 0.001) and less sedentary gain (P for trend = 0.01). Weight loss categories had a strong trend with light activity gain but not statistically significant (P for trend = 0.06). CONCLUSIONS: Small increases in MVPA and decreases in sedentary time over 2 years were associated with weight loss among adults with obesity and with or at elevated risk for knee osteoarthritis.